Cyber Security and Personal Data Protection in the Digital Age: Challenges, Impacts, and Urgency of Global Collaboration - Gardi, Bayar; Eddine, Belouadah Ahmed Seif (Bulletin of Science, Technology and Society, 2023)
Cybersecurity and personal data protection have become major issues in the rapidly growing digital era. This research aims to analyze the main challenges in cybersecurity and the urgency of personal data protection in a global perspective. The research method used is a literature study, by reviewing various academic sources and international journals that discuss aspects of digital security. The results show that increasingly complex cyber threats, lack of user awareness, and weak data protection regulations are the main factors that increase the risk of data leaks and cybercrime. In addition, global cooperation in cybersecurity is key to addressing cross-border threats. By sharing information and mitigation strategies, countries and organizations can collectively improve cyber resilience. Stricter and more transparent regulations and increased public awareness of the importance of cybersecurity are also crucial steps to reduce the risk of digital crime. Education and training of cybersecurity experts also needs to be improved to deal with evolving threats. With a more comprehensive and collaborative approach, personal data protection and cybersecurity can be better maintained in the global digital ecosystem.